2010
DOI: 10.1002/ajhb.21054
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of digit ratio 2D:4D shows greater sex difference in the right hand

Abstract: Right-hand 2D:4D might be a better indicator of prenatal androgenisation than left-hand 2D:4D. The view that 2D:4D has allometric properties (Kratochvil L, Flegr J. 2009. Differences in 2nd to 4th digit length ratio in humans reflect shifts along the common allometric line. Biol Lett 5:643-646.) is not supported. Bone lengths contribute to the sex difference in 2D:4D. In addition, there might be a sex difference in fingers' soft tissue, which should be investigated. Because of measurement unreliability, correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
410
21
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(511 citation statements)
references
References 120 publications
(77 reference statements)
72
410
21
8
Order By: Relevance
“…This side-related difference is also supported by Manning et al [43], who found stronger association between testosterone levels and 2D:4D ratios on the right hand compared with the left hand, as well as by other authors [4]. These authors hypothesize a stronger action of androgens on the digits of the right hand (see [48] for a meta-analysis).…”
Section: Discussionsupporting
confidence: 76%
“…This side-related difference is also supported by Manning et al [43], who found stronger association between testosterone levels and 2D:4D ratios on the right hand compared with the left hand, as well as by other authors [4]. These authors hypothesize a stronger action of androgens on the digits of the right hand (see [48] for a meta-analysis).…”
Section: Discussionsupporting
confidence: 76%
“…Certainly there is variance in 2D:4D ratio that cannot be attributed to prenatal testosterone alone, and sex or certain phenotypes cannot be predicted from individual digit ratios (17,29). However, 2D:4D ratio is useful for predicting human behavior when comparing groups, and has proven to be a valuable marker for individual differences in prenatal androgen exposure in correlational studies (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Another supposed retrospective indicator of relative androgen exposure during early development is the ratio between the length of the index finger and the ring finger, the 2D:4D ratio (Grimbos, Dawood, Burriss, Zucker, & Puts, 2010;Hönekopp & Watson, 2010;McFadden & Shubel, 2002;Peters et al, 2002;Williams et al, 2000). Although OAEs and digit ratios, when directly compared, showed no correlation (McFadden & Shubel, 2003;Snihur & Hampson, 2011), these two measures may provide complementary evidence for early androgenic effects on neurobiological sexual differentiation.…”
Section: Discussionmentioning
confidence: 99%